Nutrient Composition and Sensory Properties of Breakfast Cereals Produced from Millet Flour Supplemented with Soybean and Date Fruit Flours - D. L. Ahmadu; J. I. Okoye; A. E. Egbujie (Archives of Current Research International, 2023)
This study was designed to evaluate the nutrient composition and sensory properties of breakfast cereals produced from blends of millet, soybean and date fruit flour. Soybean and date fruit flours were used at varying replacement levels (5-30% soybean and 5-20% date fruit) for malted millet flour in the production of breakfast cereals with breakfast cereal produced from 100% malted millet flour as control. The nutrient composition and sensory properties of the breakfast cereals were evaluated using standard methods. The moisture, crude protein, fat, crude fibre and ash contents of the breakfast cereals increased significantly (p<0.05) with increase in substitution of soybean and date fruit flours from 7.19-7.63%, 7.69-18.32%, 3.09-4.03%, 2.47-3.86% and 1.21-2.07, respectively, while the carbohydrate and energy contents decreased from 78.37-64.13% and 371.99-365.10KJ/100g, respectively. The mineral composition of the breakfast cereals also increased significantly (p<0.05) with increase in substitution of soybean and date fruit flours from 17.86-96.52mg/100g (calcium), 58.47-132.72mg/100g (potassium), 79.01-120.76mg/100g (phosphorus), 16.54-86.54mg/100g (magnesium), 1.55-2.14mg/100g (iron) and 1.32-1.72mg/100g (zinc), respectively. The thiamine, riboflavin, niacin, ascorbic acid, vitamin A and folic acid contents of the samples equally increased significantly (p<0.05) with increase in substitution of soybean and date fruit flours from 1.36-2.57mg/100g, 2.36-3.51mg/100g, 2.14-3.56mg/100g, 1.55-2.22mg/100g, 2.23-4.26mg/100g and 1.02-1.81mg/100g, respectively. The sensory properties of the samples showed that the porridge made from the control sample (Breakfast cereal made with 100% malted millet flour) was the most acceptable to the panelists and also differed significantly (p<0.05) from those prepared from the substituted samples in colour, texture, taste and flavour. The study, however, showed that the nutrient contents and sensory properties of millet based breakfast cereals could be improved by supplementing millet flour with different proportions of soybean and date fruit flours in the preparation of nutrient-dense and acceptable breakfast cereal products.